1998
DOI: 10.1128/jvi.72.9.7349-7356.1998
|View full text |Cite
|
Sign up to set email alerts
|

Binding of Sindbis Virus to Cell Surface Heparan Sulfate

Abstract: Alphaviruses are arthropod-borne viruses with wide species ranges and diverse tissue tropisms. The cell surface receptors which allow infection of so many different species and cell types are still incompletely characterized. We show here that the widely expressed glycosaminoglycan heparan sulfate can participate in the binding of Sindbis virus to cells. Enzymatic removal of heparan sulfate or the use of heparan sulfate-deficient cells led to a large reduction in virus binding. Sindbis virus bound to immobiliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
98
0
2

Year Published

1999
1999
2006
2006

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 262 publications
(106 citation statements)
references
References 67 publications
2
98
0
2
Order By: Relevance
“…While little is known about the changes required for efficient replication of HCoV-OC43 in the murine CNS, it is likely that this process includes mutations that affect binding to host cell sugar moieties. Infection with the prototypic alphavirus, Sindbis virus (SINV), or with a picornavirus, Theiler's murine encephalomyelitis virus (TMEV), is initiated by binding to a polyanionic polysaccharide, heparin sulfate (Byrnes and Griffin, 1998;Klimstra et al, 1998;Reddi and Lipton, 2002). SINV with enhanced binding to heparin sulfate is selected after passage in tissue culture cells.…”
Section: Discussionmentioning
confidence: 99%
“…While little is known about the changes required for efficient replication of HCoV-OC43 in the murine CNS, it is likely that this process includes mutations that affect binding to host cell sugar moieties. Infection with the prototypic alphavirus, Sindbis virus (SINV), or with a picornavirus, Theiler's murine encephalomyelitis virus (TMEV), is initiated by binding to a polyanionic polysaccharide, heparin sulfate (Byrnes and Griffin, 1998;Klimstra et al, 1998;Reddi and Lipton, 2002). SINV with enhanced binding to heparin sulfate is selected after passage in tissue culture cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, specialization for replication in the hamster host resulted in rapid increases in virus fitness with many mutations, consistent with virus adaptation and evolutionary constraints imposed by the alternating-host cycle of arboviruses 88 . Cell-culture models probably do not fully reflect in vivo conditions, as artefacts (such as selection for virus binding to heparin sulphate) might distort results 89,90 .…”
Section: Dengue Virusmentioning
confidence: 99%
“…The inconsistencies in the results described above from different studies suggest limitations in the cell culture model systems used to study arbovirus evolution. In addition, artifactual adaptation events mediated by binding of some arboviruses to unnatural receptors such as glycosaminoglycans (Byrnes and Griffin 1998;Klimstra et al 1998;Hilgard and Stockert 2000), which are found on the surface of both vertebrate and invertebrate cells, suggest that selection conditions in vivo might yield different results and conclusions.…”
Section: Constraints Of the Arbovirus Transmission Cycle On Adaptatiomentioning
confidence: 99%